The evolution of the Chitty - Ravichandran Moorthy (Penerbit UKM, 2009)
The Chittys or Peranakan Hindu of Melaka (also known as the Melaka Straits-born Hindus) is a hybrid community that emerged from inter-marriages between the Hindu traders and local Malays, Chinese, Javanese and Bataks. This community, domiciled in Melaka, has been around since the reign of the Melaka Sultanate in the early 15th century. Even before the arrival of Parameswara (a Hindu prince from Palembang, Sumatra) in 1401, spice traders (largely Hindus) from India had already visited and traded in Melaka port. Growing trade with the Malay world, especially in Melaka attracted many Indians, especially traders from the Coromandel Coast in India to settle in Melaka. The most unique feature of this community is the extent to which they have assimilated to the culture of the indigenous Malays. In their choice of clothing, spoken language, food and perhaps appearance, they bear resemblance to the Malays and Baba Nyonyas (the Melaka Straits-born Chinese). However, despite the onslaught of Islam and Christianity in the city state, the Chittys have steadfastly remained Hindus. Although they have lost their roots with India and became inarticulate in Tamil (the Indian language), they have held on to their Hindu names and consistently observe customary and religious practices. Despite their long presence in Melaka and active contributions in trade and in the politics of Melaka, the community has been largely ignored by the rest of the society. This article attempts to capture the evolution and transformation of this community from the days of the Melaka Sultanate to the post independence era of modern Malaysia.